2010
DOI: 10.1111/j.1550-7408.2010.00522.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, Morphometrics, and Molecular Characterization of Bryophrya gemmea n. sp. (Ciliophora, Colpodea): Implications for the Phylogeny and Evolutionary Scenario for the Formation of Oral Ciliature in the Order Colpodida

Abstract: We studied the morphology, morphometry, resting, and reproductive cysts, as well as the molecular phylogeny of Bryophrya gemmea n. sp., a colpodid ciliate that was discovered in ephemeral puddles in Idaho, northwest United States. This new species is distinguished from congeners by the irregularly pentagonal adoral organelles, four to five vestibular kineties, the single micronucleus, and one to three rows of brightly refractive protuberant interkinetal cortical granules to the right of the preoral suture. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…In congruence with Bourland et al (2011), Foissner et al (2011) found the Marynidae s.l. to be non-monophyletic.…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…In congruence with Bourland et al (2011), Foissner et al (2011) found the Marynidae s.l. to be non-monophyletic.…”
Section: Introductionmentioning
confidence: 70%
“…Recently, Bourland et al (2011) sequenced Maryna ovata , and showed that it did not form a monophyletic clade with the previously sampled Marynidae, Ilsiella palustris . However, only one of two intervening nodes between these two species was moderately supported, with 76% bootstrap by Maximum Likelihood (ML) and a posterior probability of 100% by Bayesian Inference (BI).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations